2010
DOI: 10.1001/archneurol.2010.58
|View full text |Cite
|
Sign up to set email alerts
|

Marked Hemiatrophy in Carriers of Duchenne Muscular Dystrophy

Abstract: Objective: To describe the clinical and molecular genetic findings in 2 carriers of Duchenne muscular dystrophy (DMD) who exhibited marked hemiatrophy. Duchenne muscular dystrophy is an X-linked disorder in which affected male patients harbor mutations in the dystrophin gene. Female patients with heterozygous mutations may be manifesting carriers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 7 publications
1
11
0
Order By: Relevance
“…This early event could explain the preferential segregation of dystrophin‐negative fibers on that side. However, we cannot exclude a contribution of somatic mosaicism in some of our cases, as already suggested in patients with marked hemiatrophy .…”
Section: Discussionmentioning
confidence: 52%
“…This early event could explain the preferential segregation of dystrophin‐negative fibers on that side. However, we cannot exclude a contribution of somatic mosaicism in some of our cases, as already suggested in patients with marked hemiatrophy .…”
Section: Discussionmentioning
confidence: 52%
“…This pattern is typically seen with female carriers of DMD, 8 however, the proband was male. Histopathology showed a remarkably variable dystrophic myopathy, with some regions showing normal histology, and others a marked dystrophic picture by both hematoxylin eosin and Gomori's-modified trichome methods (Figure 1c).…”
Section: Case Reportmentioning
confidence: 74%
“…More recently, Rajakulendran et al [] reported on two unrelated women exhibiting hemiatrophy due to Duchenne muscular dystrophy (DMD), showing striking muscle wasting of right arm and leg. The authors reported co‐existence of reduced dystrophin and increased utrophin expression in scattered fibers from the right quadriceps biopsies in Patient 1, and a mosaic expression of dystrophin‐positive and dystrophin‐negative fibers in the right‐sided affected deltoid muscle biopsies in Patient 2 whose left‐sided muscles only showed “sporadic” dystrophin‐negative fibers.…”
Section: Resultsmentioning
confidence: 99%
“…A literature search was conducted for all molecular genetics, cytogenetics, and cell biology studies on mutation‐induced morphological, physiological, and developmental asymmetries. This survey yielded papers reporting the distributions of male and female cells in bilateral gynandromorphic animals [Agate et al, ; Zhao et al, ], and in human hermaphrodites [Gartler et al, ], the distributions of labeled cells in cell lineage traced animals [Klein, ; Danilchik and Black, ; Masho, ; Summers et al, ; Nutt et al, ], the distributions of the mutation‐carrying cells in patients with mutation‐induced diseases that affected an entire or almost one entire lateral body half of the patients [König et al, ; Li et al, ; Rajakulendran et al, ], and mutation‐carrying cell allocations in MZ twins of complete discordance [Sakuntabhai et al, ; Kondo et al, ; Robertson et al, ; Vadlamudi et al, ], partial discordance [Costa et al, ; Weksberg et al, ; Bliek et al, ], and mirror‐image discordance [Morison et al, ; Helland and Wester, ; Zhou et al, ]. Images depicting the distributions of morphological asymmetries and labeled cells were visually inspected and interpreted.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation